Pengembangan Zona Edukasi Konservasi Satwa Liar Berbasis Masyarakat di Negeri Suli, Kabupaten Maluku Tengah - Lesly Latupapua; Cornelis Karel Pattinasarany (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Maluku region, particularly Negeri Suli in Central Maluku Regency, boasts high biodiversity, with endemic species such as the Moluccan parrot, the Moluccan cockatoo, and the cuscus. However, community inactivity and low environmental awareness pose challenges to conservation. This community service initiative aims to increase community understanding and participation in wildlife conservation through the development of a community-based education zone. The method used is a participatory approach through preparation, outreach, education, and community involvement in planning and management. Results show that the conservation education zone is able to increase environmental awareness, strengthen the community's role in wildlife protection, and encourage the application of local wisdom such as sasi in natural resource management. Furthermore, this zone has the potential to become a learning platform, research platform, and economic development through ecotourism. Thus, the development of a community-based conservation education zone is an important strategy to support biodiversity conservation and improve community welfare in a sustainable manner.